2012
DOI: 10.1017/s0143385712000247
|View full text |Cite
|
Sign up to set email alerts
|

Robust transitivity for endomorphisms

Abstract: We address the problem about under what conditions an endomorphism having a dense orbit, verifies that a sufficiently close perturbed map also exhibits a dense orbit. In this direction, we give sufficient conditions, that cover a large class of examples, for endomorphisms on the n−dimensional torus to be robustly transitive: the endomorphism must be volume expanding and any large connected arc must contain a point such that its future orbit belong to an expanding region.Date: September 21, 2018. † This work wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Moreover, C 1 generically in the space of local diffeomorphisms with no splitting and all points with dense pre-orbits, there are uncountably many ergodic expanding invariant measures with full support and exhibiting exponential decay of correlations. In particular, these results hold for an important class of robustly transitive maps considered in [7].…”
mentioning
confidence: 61%
See 3 more Smart Citations
“…Moreover, C 1 generically in the space of local diffeomorphisms with no splitting and all points with dense pre-orbits, there are uncountably many ergodic expanding invariant measures with full support and exhibiting exponential decay of correlations. In particular, these results hold for an important class of robustly transitive maps considered in [7].…”
mentioning
confidence: 61%
“…Note that Lemma 4.1 proves the robustness of IRG property, which is fundamental to prove the density of the pre-orbit of any point under the perturbed map. For further details, see [7]. After the discussion above, we are now in condition to present a large class of examples that illustrate our main results.…”
Section: 1mentioning
confidence: 76%
See 2 more Smart Citations
“…Based on the examples of robustly transitive diffeomorphisms were constructed robustly transitive non-expanding endomorphisms. In [LP13] were obtained necessary and sufficient conditions for robustly transitive local diffeomorphisms. In particular, it is shown that it is not necessary any weak form of hyperbolicity for robustly transitive; a trivial example is an expanding linear endomorphism with complex eigenvalues, which does not admit a dominated splitting.…”
Section: Introductionmentioning
confidence: 99%